Garbage Bin Optimization using IoT, RFID and a Crusher Mechanism - Praveen M, Beryl Caleb S, Mrs.J.Jayapradha (International Journal of Advanced Science and Technology, 2020)
IoT is a system of connected computing devices, machines, digital systems, and transfer the data across the network without human intervention. Increasingly, organizations across the globe started using IoT for efficient results. IoT automates the process and thus reduces the labor cost. Using IoT, we have introduced a concept that is an optimized garbage system. It uses various applications like the Internet Of Things (IoT), Radio Frequency Identification(RFID), and crusher machines in the garbage to crush the waste to smaller particles. The IoT is used to send and receive information such as the state of the bin, density of the contents, real-time working mechanisms, and much more. RFID is used to tag the container with an identification code to identify the garbage container separately. When the garbage truck arrives to collect the garbage from the garbage bin,  the truck identifies the fully loaded bin using the tag on each bin. When the garbage truck comes close to the garbage bin, it recognizes and beeps, which reduces the stress to open and see each bin separately. Since the IoT keeps the system updated with information, there is no need for human resources to inspect the garbage cans regularly. IoT can be operated by using the Arduino kit, which has ArduinoIDE microprocessors and microcontrollers with all programmed information and commands that drive the functions of IoT. For real-time monitoring of the bin, the IoT must be connected to a secure Wi-Fi connection to be updated every time to send the information. The overall idea is to collect the trash in a crushed manner to make it easy for recycling. It reduces the work of collecting the overflowing bins. The RFID can identify the overflowing Garbage bin fixed on the containers.  It helps in better recycling and disposal of waste, creating a cleaner environment, and a better eco-system. Keywords: Internet of Things (IoT), IoT, RFID, Garbage bin, Wi-fi, Arduino IDE.